H-coil repetitive transcranial magnetic stimulation does not improve executive function in patients with chronic peripheral neuropathic pain: a randomized sham-controlled crossover study - Farnes, Nadine; Jacobsen, Henrik B.; Stubhaug, Audun; Vambheim, Sara M. (Frontiers in Psychiatry, 2024)
Introduction: Deep rTMS is an increasingly popular noninvasive brain stimulation technique which has shown promise for treating cognitive impairments. However, few studies have investigated the cognitive effects it could exert in patients with chronic peripheral neuropathic pain. Therefore, we aimed to assess the effects of deep rTMS on executive functioning in patients with peripheral neuropathic pain, in a randomized, double-blind crossover trial. Methods: In total 17 patients were randomly assigned to receive both active and sham deep H-coil rTMS targeting the primary motor cortex. Each treatment period consisted of five daily rTMS sessions. Selected tests of executive functioning from the CANTAB test battery (paired associates learning, stop signal task, spatial working memory and multitasking test) were performed at baseline, and at 1 week and 3 weeks follow-ups. Results: We did not find any significant interactions between time and treatment for the measures of executive functioning for the patient group, or for patients with reduced cognition compared to normative means. Conclusion: High-frequency deep H-coil rTMS targeting the hand area of the primary motor cortex and delivered over 5 consecutive days did not improve executive functioning in patients with chronic peripheral neuropathic pain.